Globalization : Perak's rise, relative decline, and regeneration - Shah, Nazrin (Oxford : Oxford University Press, 2024)
A pioneering study of the many economic and social changes in the natural resource-rich Malaysian state of Perak over the last two centuries, this book brings together multiple sub-themes that have driven Perak's fortunes in sometimes dramatic economic cycles and concludes by looking forward at how Perak can regenerate itself once more.
Includes bibliographical references and index.
Specialized.
Description based on online resource and publisher information; title from PDF title page (viewed on April 2, 2024).
Keywords: Perak (Malaysia) -- History